INNOVATION WORK BEHAVIOR IN THE DIGITAL ERA: A SYSTEMATIC LITERATURE REVIEW - Handiman, Unang Toto; Adam, Duki (Ultima Management : Jurnal Ilmu Manajemen, 2024)
Abstract- The digital era has transformed organizational dynamics, necessitating innovative work behavior (IWB) as a key driver of competitive advantage. This study systematically reviews the role of technology and organizational culture in shaping IWB, focusing on their interplay and implications for organizations. The objective is to understand how technological advancements influence IWB and how aspects of organizational culture can enhance or inhibit this behavior in the digital era. Despite the growing emphasis on IWB, there is limited understanding of how technology and organizational culture jointly influence it, creating gaps in both theory and practice. This paper integrates insights from diverse studies to highlight the synergy between technology and organizational culture, proposing that their interplay is pivotal for fostering IWB. A systematic review approach was employed, synthesizing findings from peer-reviewed articles, reports, and case studies to identify trends, relationships, and critical gaps. The findings reveal that technology facilitates IWB by enabling collaboration, real time decision-making, and innovative problem-solving. However, its potential is moderated by organizational culture factors such as leadership support, openness to change, and psychological safety significantly enhance or constrain IWB. The study identifies the need for a balanced approach that aligns technological capabilities with cultural readiness. This review underscores the interdependence of technology and organizational culture in fostering IWB and highlights critical gaps and future research opportunities. Addressing these gaps can guide organizations in effectively leveraging technology and culture to sustain innovation in the digital era. Keywords: Innovation Work Behavior; Digital Era; Organizational Culture; Systematic Literature Review